Patient Preferences About Immediate Postpartum Long-Acting Reversible Contraception: A Qualitative Study [10F]. (May 2017) - Soliman, Ann; Dalton, Vanessa; Moniz, Michelle
Abstract : INTRODUCTION: To acquire in-depth understanding about patient preferences regarding the timing of long-acting reversible contraceptive (LARC) insertion after childbirth. METHODS: We conducted semi-structured interviews with pregnant women planning to use LARC postpartum (n=5). Participants watched a standardized video explaining LARC insertion timing options. Interviews were audio recorded, transcribed verbatim, and coded by two authors (AAS, MHM) using qualitative content analysis. RESULTS: Interviewees identified a variety of personal preferences for timing of LARC insertion. Cited reasons for preferring immediate postpartum insertion (n=3 women) included strong desire to prevent rapid repeat pregnancy, wanting to initiate contraception prior to being occupied with a new baby, and ability to address potential issues with their LARC device at the postpartum visit. Women (n=2) preferring outpatient insertion reported wanting to let the body recuperate after childbirth before initiating contraception and concern about expulsion and potential risks to breastfeeding with immediate insertion. Regardless of personal preferences for timing of insertion, all interviewees supported making immediate postpartum insertion available to women. Participants reported enthusiasm for discussing contraceptive options with any provider at any time during their prenatal care visits and expressed an affinity for receiving information via in-person conversations and visual formats (e.g. video, pamphlets) that could be shared with a partner. CONCLUSION: Our findings suggest that pregnant women have a range of preferences regarding timing of postpartum LARC insertion and support making immediate postpartum insertion available to women who desire it. Enhancing access to this service may align with women's contraceptive preferences and enhance their ability to meet their reproductive goals.